2015
DOI: 10.2147/amep.s73644
|View full text |Cite
|
Sign up to set email alerts
|

Improving medical students' knowledge of genetic disease: a review of current and emerging pedagogical practices

Abstract: Genetics is an essential subject to be mastered by health professional students of all types. However, technological advances in genomics and recent pedagogical research have changed the way in which many medical training programs teach genetics to their students. These advances favor a more experience-based education focused primarily on developing student’s critical thinking skills. In this review, we examine the current state of genetics education at both the preclinical and clinical levels and the ways in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 61 publications
3
27
0
2
Order By: Relevance
“…It is important because while RD are life threatening and chronically debilitating diseases that significantly reduce patients' quality of life, their early detection, diagnosis and therapy enable the patient's daily functioning and increase their quality of life. Thus, although during the past few years there have been an increasing number of campaigns and initiatives aiming at addressing RD, including celebration of Rare Disease Day on February 29 th (which was first organized in 2008 in numerous European countries and in Canada), and creation of many websites dedicated to RD and their particular types, still there can be observed a lack of knowledge about RD among the general population (9,10), medical students (11)(12)(13)(14)(15)(16) and healthcare professionals, including physicians and pharmacists (17)(18)(19)(20)(21)(22). Consequently, RD patients and their families report that due to physicians' lack of knowledge and disease-related experience they have to become selfexperts on their own disease and educate physicians about their condition (18,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…It is important because while RD are life threatening and chronically debilitating diseases that significantly reduce patients' quality of life, their early detection, diagnosis and therapy enable the patient's daily functioning and increase their quality of life. Thus, although during the past few years there have been an increasing number of campaigns and initiatives aiming at addressing RD, including celebration of Rare Disease Day on February 29 th (which was first organized in 2008 in numerous European countries and in Canada), and creation of many websites dedicated to RD and their particular types, still there can be observed a lack of knowledge about RD among the general population (9,10), medical students (11)(12)(13)(14)(15)(16) and healthcare professionals, including physicians and pharmacists (17)(18)(19)(20)(21)(22). Consequently, RD patients and their families report that due to physicians' lack of knowledge and disease-related experience they have to become selfexperts on their own disease and educate physicians about their condition (18,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Presentations must describe the invaluable role that molecular testing played in diagnosis and/or clinical management of the cases discussed, and content is evaluated by the curriculum director. The inclusion of resident presentations into the curriculum is based on evidence that ‘problem‐based’ learning modalities enhance the educational experience . Use of case studies is reported to improve both the fundamental understanding of genetic principles and student confidence in the use and interpretation of molecular tools in future clinical practice …”
Section: Resultsmentioning
confidence: 99%
“…To combat this lack of competency, medical schools have now started to make a concerted effort to better integrate these concepts into their curricula . These emerging pedagogical practices emphasize the importance of combining a strong foundation in basic sciences content with applied experience‐based education in order to develop a student's critical thinking skills . It is essential for molecular genetics instruction to extend into residency training and beyond.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One theme in the free responses elucidated a potential reason for this, ‘we don't have a geneticist within 3 hr of our area. The waiting list for genetics is also 9 months…We encourage patients to share their [NIPT] result with their pediatrician.’ A 2015 study stated that 50% of medical genetics residencies remain unfilled, leading to fewer clinical geneticists today than 30 years ago (Allyse et al, ; Wolyniak, Bemis, & Prunuske, ). Therefore, while all individuals with positive NIPT should have follow‐up at birth, referring these patients to a medical geneticist may put increased strain on an already limited resource.…”
Section: Discussionmentioning
confidence: 99%